PENGARUH KEPUASAN KERJA DAN KEPRIBADIAN TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL PEMEDIASI (STUDI KASUS PADA KARYAWAN PT. BHUMI MERAPI AGROWISATA) - Rahmawati Riantisari; arifin arifin; Farruk Rastha Pradipta (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2021)
This study aims to determine the effect of job satisfaction and personality on Organizational Citizenship Behavior (OCB) with organizational commitment as a mediating variable: a case study on PT. Bhumi Merapi Agrowisata(2019). This study uses a causal relationship, while the analytical tool used is path analysis. Data taken through the distribution of questionnaires given to all employees of PT. Bhumi Merapi Agrowisata totaling 30 people. The results showed that job satisfaction has a positive effect on OCB, job satisfaction has a positive effect on organizational commitment, personality has a positive effect on OCB, personality has a positive effect on organizational commitment, organizational commitment has a negative effect on OCB and organizational commitment is a mediating variable of the effect of job satisfaction and personality on OCB. As an improvement effort, it is suggested by PT. Bhumi Merapi Agrowisata to enhance OCB behavior, it is suggested to pay more attention to the organizational commitment of its employees through providing job satisfaction. Keywords: job satisfaction, personality, organizational commitment, organizational citizenship behavior (OCB), causal relationships, path analysis